Civil-Military Cooperation in Disaster Management - Sutopo Purwo Nugroho; Tika Savitri Pandanwangi; Suprapto Suprapto (The Republic of Indonesia Defense University, 2016)
During Jakarta flood from 2013 to 2015, emergency response optimized roles of military and civil. Civil-military coordination is a mechanism in disaster management in term of accelerating response and minimizing number of victim and damage as well. The aim of this study is to analyze and describe the system of coordination and civil-military cooperation in emergency response Jakarta flood from 2013 to 2015 and find optimal form of cooperation and coordination emergency response of civil-military in the Jakarta flood 2013. This qualitative research is a descriptive research with data collection techniques is literature review and in-depth interviews. The results showed that the civil-military coordination in the flood disaster can be run either although the difference between commando and grammar used in the civil-military provide constraints in emergency operations.